2023
DOI: 10.15252/embj.2022113410
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of LRRK2 mRNA stability by ATIC and its substrate AICAR through ARE‐mediated mRNA decay in Parkinson's disease

Abstract: Mutations in LRRK2 are the most common genetic causes of Parkinson's disease (PD). While the enzymatic activity of LRRK2 has been linked to PD, previous work has also provided support for an important role of elevated LRRK2 protein levels, independent of enzymatic activity, in PD pathogenesis. However, the mechanisms underlying the regulation of LRRK2 protein levels remain unclear.Here, we identify a role for the purine biosynthesis pathway enzyme ATIC in the regulation of LRRK2 levels and toxicity. AICAr, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…2). We found that in G2019S L2PD a number of proteins expression was reduced namely, ATIC, which can repress LRRK2 and rescue neurodegeneration 48 (log2FC=-0.97, adj. P=1.92x10 -13 ); RAB9A, involved in phagocytic vesicle trafficking and lysosomal function (log2FC=-1.17, adj.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…2). We found that in G2019S L2PD a number of proteins expression was reduced namely, ATIC, which can repress LRRK2 and rescue neurodegeneration 48 (log2FC=-0.97, adj. P=1.92x10 -13 ); RAB9A, involved in phagocytic vesicle trafficking and lysosomal function (log2FC=-1.17, adj.…”
Section: Resultsmentioning
confidence: 98%
“…61 Thus, ATIC, the top protein down-regulated in G2019S carriers, catalyses the last two steps of mitochondria purine biosynthesis 62,63 and was also linked previously to LRRK2 toxicity. 48 Other deficits included KARS1, a tRNA synthetase; PSMC5, the proteasomal 26S subunit; or SCLY, seleno-cysteine lyase, an enzyme involved in peptide elongation that is also involved in neurodegeneration. 64 Our findings in LRRK2 PMBCs align with studies reporting transcriptional repression of proteostasis regulators in G2019S L2PD, 65 and proteostasis defects in PD substantia nigra.…”
Section: Discussionmentioning
confidence: 99%